2017
DOI: 10.1038/nn.4516
|View full text |Cite
|
Sign up to set email alerts
|

Video-rate volumetric functional imaging of the brain at synaptic resolution

Abstract: Neurons and neural networks often extend hundreds to thousands of micrometers in three dimensions. To capture all the calcium transients associated with their activity, we need volume imaging methods with sub-second temporal resolution. Such speed is challenging for conventional two-photon laser scanning microscopy (2PLSM) to achieve, because of its dependence on serial focal scanning in 3D and the limited brightness of indicators. Here we present an optical module that can be easily integrated into standard 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
199
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(200 citation statements)
references
References 60 publications
1
199
0
Order By: Relevance
“…The most common approach involves the use of an axicon (conical lens) [8, 9, 10]. Other approaches employed a phase mask [11], or alternatively a spatial light modulator (SLM) [12], with the latter allowing for great flexibility in generating different types of Bessel foci with shaped axial intensity profiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common approach involves the use of an axicon (conical lens) [8, 9, 10]. Other approaches employed a phase mask [11], or alternatively a spatial light modulator (SLM) [12], with the latter allowing for great flexibility in generating different types of Bessel foci with shaped axial intensity profiles.…”
mentioning
confidence: 99%
“…Previous observations showed that, for two-photon fluorescence microscopy, lower-NA (e.g., 0.4 or 0.6) Bessel foci produced better-quality images of brains in vivo [12]. For high-NA Bessel foci (e.g., 0.9), more energy is distributed in the side rings, causing a stronger background and image blur.…”
mentioning
confidence: 99%
“…In other words, the volumetric information is projected into a single 2D image. As such, extended depth of focus (EDF) imaging can be attractive to image sparsely populated structures rapidly and has found promising applications in functional imaging of neuronal activity [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Various beam shaping methods have been successfully employed for EDF imaging, which involve different amplitude, phase or combined filters in the pupil plane [3][4][5], and in some cases also feature specialized optical elements such as axicons [6,7]. Their implementation typically requires significant changes to a conventional microscope [1]. Further, if phase modulation is used, the associated phase masks or holograms are typically wavelength dependent, which prevents, or at least complicates, multi-color imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the operation of these circuits has been greatly advanced by using multiphoton microscopy to image fluorescent reporter proteins that signal events such as changes in cytoplasmic calcium, reflecting spiking activity (Tian et al, 2012), or the release of glutamate at excitatory synapses (Marvin et al, 2013). At present, the large majority of in vivo imaging studies quantify activity as calcium signals in the soma of neurons but we also need to image activity across populations of synapses if the operations of neural circuits are to be unravelled (Lu et al, 2017;Kazemipour et al, 2019;Meng et al, 2019). These connections are key components of all the computations within neural circuits and sites at which neuromodulators act to reconfigure signal flow according to changes in the internal state of the animal.…”
Section: Introductionmentioning
confidence: 99%